MAKNA KARANTINA DALAM PERSPEKTIF PERJANJIAN LAMA DAN RELEVANSINYA DENGAN KARANTINA DI MASA PANDEMI COVID-19 - Restifani Cahyami; Neneng Andriani; Resta Gloria (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
The purpose of this study is to find and explain the meaning of quarantine according to the Old Testament and its relevance to quarantine during the Covid-19 pandemic. The research method used is a descriptive qualitative method through literature studies and through a hermeneutic approach to finding the meaning of quarantine in the Old Testament. This article shows that quarantine in the Old Testament was a form of obligation and provision that was commanded by God to his people with the aim of providing goodness for people's lives specifically in certain situations faced by God's people. Based on the meaning and purpose of quarantine according to the Old Testament, it is found that the quarantine carried out in the Old Testament is related to quarantine during the Covid-19 pandemic where through quarantine God's love for humans and human love for other humans can be realized by looking after and protecting each other. in the midst of a threatening Covid-19 pandemic situation. Therefore, quarantine in the Old Testament and quarantine in the midst of the Covid-19 pandemic are a form of love for God, oneself, and others.